Whole genome sequencing and genome comparison of closely related Bacillus species isolated from the environment - Foo, Cyrus Jit Loong (Nanyang Technological University, 2020)
Basal stem rot or Ganoderma Boninense is a fungal disease that degrades the lignin, found in the trunks of oil palms which can cause oil palms to collapse. This can lead to great reduction in yield and economic losses. Biological control agents from the species of Bacillus have been identified as potential, short term antifungal solutions against the disease. This employ the use of plant growth-promoting bacteria which can produce various antimicrobial metabolites to improve the plant’s defense mechanisms against plant pathogens. The performance of these bacterium depends on the strains used, as different strains from the same species of Bacillus can yield different levels of performance. From a previous study, 11 strains from environmental samples was previously identified using 16S rRNA sequencing and Sanger’s method of sequencing, but this provided insufficient information to differentiate closely-related Bacillus species. Whole Genome Sequencing, which is based on next generation sequencing by Illumina was employed to obtain better genome drafts. This provided more accurate results on the genome of the sequenced strains, such as their taxonomy, % genome content (GC) and assembled genome size. Bioinformatic tools were also used to analyze the sequenced data to identify potential antimicrobial genes in the sequenced strains. The bioinformatic tools used produced good quality data for downstream analysis. This can be seen from average coverage of at least a 100 times for each strain and the high Phred quality scores (Qscore) of Q35 which corresponded to more than 99.9% accuracy during sequencing. The results showed good quality contigs that were long, few in number and were separated into the 3 clusters, according to their assembled genome size and %GC content. Phylogenetic analysis performed subsequently confirmed the identity of 3 strains - B. velezensis, B. subtilis and B. megaterium. The antimicrobial genes identified were categorized into 10 sets of genes and 2 sets of genes were uniquely found (from BSF1B11 strain) to have antibiotic properties.